2022
DOI: 10.1073/pnas.2101117119
|View full text |Cite
|
Sign up to set email alerts
|

Mutant libraries reveal negative design shielding proteins from supramolecular self-assembly and relocalization in cells

Abstract: Understanding the molecular consequences of mutations in proteins is essential to map genotypes to phenotypes and interpret the increasing wealth of genomic data. While mutations are known to disrupt protein structure and function, their potential to create new structures and localization phenotypes has not yet been mapped to a sequence space. To map this relationship, we employed two homo-oligomeric protein complexes in which the internal symmetry exacerbates the impact of mutations. We mutagenized three surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Our results demonstrate how a small number of residues—only seven mutations—can enable an increase in oligomeric state, providing insight into the requisite degree of plasticity necessary for innovation of larger oligomeric states. Recent studies have demonstrated how few mutations can be introduced to proteins, resulting in radical increases in oligomerization that are more accurately described as non-native protein fibrils ( 27 29 ). In comparison, our study focuses on understanding the structural basis underlying transitions between oligomeric states found in nature, as our mutational engineering of the 2-to-6 enzyme recapitulates the evolutionary trajectory taken by form II RuBisCOs when assembling hexamers from dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate how a small number of residues—only seven mutations—can enable an increase in oligomeric state, providing insight into the requisite degree of plasticity necessary for innovation of larger oligomeric states. Recent studies have demonstrated how few mutations can be introduced to proteins, resulting in radical increases in oligomerization that are more accurately described as non-native protein fibrils ( 27 29 ). In comparison, our study focuses on understanding the structural basis underlying transitions between oligomeric states found in nature, as our mutational engineering of the 2-to-6 enzyme recapitulates the evolutionary trajectory taken by form II RuBisCOs when assembling hexamers from dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate how the nature of evolution, in only selecting for 'good enough', rather than fully optimized systems, results in small margins in specificity, and actually constrains the subsequent evolvability of paralogous families. This principle also applies to protein stability 21,43 , abundance 44 , and localization and assembly properties 45 . In each case, a large proportion of substitutions can disrupt the relevant property, suggesting that robustness has not evolved in these traits.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that genetic suppression in a yeast model of the disease has also been reported, where deletion 29 or missense mutations on the regulatory domain 29 can overcome the deleterious effects of the most common HCU mutations. Disease associated mutants in general can produce hydrophobic patches in the protein due to local misfolding, that will result in aggregation [48][49][50] . It is probable that many HCU mutations generate hydrophobic patches on the catalytic domain resulting in further non-specific interactions that lead to aggregation 19 (Fig.…”
Section: Discussionmentioning
confidence: 99%